2008
DOI: 10.2466/pr0.103.2.459-466
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse Related to Nicotine, Illicit and Prescription Drug use by Women: Pilot Study

Abstract: A sample of 811 women ages 18 to 59 (M=26.0, SD=6.5) responded to an advertisement by telephone. Inquiries were made about childhood abuse status and adult use of alcohol, nicotine, and prescription and illicit drugs. Significant associations were noted for reported sexual, physical, and emotional childhood abuse with use of nicotine, marijuana, and antidepressants in adulthood. Reported childhood physical and emotional abuses were also significantly associated with use of cocaine and anxiolytics, and sexual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…22 Furthermore, familial experiences within this population of women are typically marked by higher than average rates of parental death, discord, divorce, desertion, substance abuse, and physical, emotional, and sexual abuse. 23,24 In addition to traumatic life events, our study participants faced multiple additional risk factors that threatened to jeopardize their well-being. For example, many of the women reported having been diagnosed with a mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Furthermore, familial experiences within this population of women are typically marked by higher than average rates of parental death, discord, divorce, desertion, substance abuse, and physical, emotional, and sexual abuse. 23,24 In addition to traumatic life events, our study participants faced multiple additional risk factors that threatened to jeopardize their well-being. For example, many of the women reported having been diagnosed with a mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, several of the women in our study had been incarcerated at least once for drug charges and/or prostitution. For these women, mothering was complicated by the complexities of living with an SUD, previous trauma, mental illness, and limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, traumatic childhood events (e.g., sexual or physical abuse) are associated with high rates of cigarette smoking and nicotine dependence in adulthood [9, 10]. For example, a comparison of current smokers to non-smokers (N=57) without other psychiatric disorders or SUDs indicated that current smokers were more likely to have experienced severe abuse as a child and individuals exposed to childhood trauma were four times more likely than individuals not exposed to childhood trauma to smoke cigarettes as an adult [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, individuals who report physical and emotional abuse as children are more likely to use cocaine as adults [9]. Additionally cocaine users report more traumatic events and more symptoms than individuals who use alcohol [1, 15].…”
Section: Introductionmentioning
confidence: 99%
“…30 Some studies have found significant relations between childhood maltreatment and substance use in women samples. 31,32 When stratifying according to sex, some studies do not find sex differences, 30 while others do note differences. 14 For example, in a cocaine treatment-seeking sample, greater severity of childhood emotional abuse increased the likelihood of cocaine relapse for women, but not for men.…”
mentioning
confidence: 99%